Two new marine flatworms (Platyhelminthes: Rhabditophora: Proseriata) of the genus Otoplana Du Plessis, 1889 from the upper Tuscany sandy shores (Italy) - Meini, Gianluca (Zootaxa, 2013)
Two new otoplanid species, from the interstitial habitats of the North-Western Mediterranenan sea coast, are described. The specimens show the typical morphological peculiarities of the subfamily Otoplaninae ("Turbellaria", Otoplanidae), but clearly differ from other species described in this group. Otoplana labronica sp. nov. is characterized by a body length of 1.2–1.5 mm, different features of the testes and vitellaries, the male sclerotic apparatus composed of a median aculeus (52–53 μm long) and 16 peculiar spines (19–44 μm long). This new species has the smallest number of spines (17) and the smaller body length, in comparison to all the species of the genus. Otoplana falcataspina sp. nov. is characterized by a body length of 2.3–2.4 mm, distinctive dimensions and arrangement of the vitellaries, the male sclerotic apparatus composed of a median aculeus (50–51 μm long) and 20–21 spines (22–44 μm long). This new species has a limited body length, and only the sexually mature specimens of the new species O. labronica exhibit a smaller size. They were collected below the low water mark on the sandy beaches at Calambrone and Marina di Vecchiano (Pisa, Ligurian Sea, Italy), respectively.